2017
DOI: 10.1002/met.1667
|View full text |Cite
|
Sign up to set email alerts
|

Future extreme rainfall change projections in the north of Iran

Abstract: Future changes in extreme rainfall arising from climate change may have a significant influence on flood and water erosion control and management strategies to a great extent. The maximum daily rainfall time series were projected for 2020-2049 using six general climate models and two scenarios through artificial neural networks for 22 stations across the north of Iran. The results indicate a reduction of between −3.0 and −0.2% in maximum rainfall for the selected stations and five out of six of the general cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 24 publications
(30 reference statements)
2
7
0
Order By: Relevance
“…Modarres et al . (2018) reported a reduction in maximum precipitation for the period 2020–2049 in the north of Iran, which can confirm our results. Vaghefi et al .…”
Section: Resultssupporting
confidence: 92%
“…Modarres et al . (2018) reported a reduction in maximum precipitation for the period 2020–2049 in the north of Iran, which can confirm our results. Vaghefi et al .…”
Section: Resultssupporting
confidence: 92%
“…In the studies of the impact of climate change, most previous projections have been conducted at the decadal time scale to show the trend of changes in temperature and precipitation at the mid to end of the 21 st century 2529 . However, extremely dry and wet periods, as well as floods in intra-annual temporal scale in arid and semi-arid countries, like Iran, have not been thoroughly studied, even though their impacts have been severe.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, in some studies, by contrast, a rise in the future precipitation has been reported. For instance, Modarres et al (2018) projected the variability of the maximum daily rainfall across the North and Northwest of Iran for 2020–2049 using six GCMs under the two scenarios A2 and B1. In particular, their results suggest the projected precipitation to vary from −16 to 7% under scenario A2, compared with the reference period (1981–2010).…”
Section: Resultsmentioning
confidence: 99%